Laparoscopic resection versus myolysis in the management of symptomatic uterine adenomyosis: alternatives to conventional treatment (Medical Journal of Indonesia, 2006)
Effective therapy preserving reproductive function in adenomyosis is warranted. From June 2003 to June 2004, patients diagnosed as having adenomyosis by transvaginal ultrasound and had symptoms of menorrhagia, dysmenorrhea, and pelvic pain were randomly allocated to either receive laparoscopic resection or myolysis. GnRH analog was given for 3 cycles after surgery. Within 6 months, symptoms were evaluated using questionnaires and at the end of follow up, adenomyosis volume was assessed by transvaginal ultra-sound. There were 20 patients included, 10 patients had resection and the rest underwent myolysis. Both procedures did not yield sig-nificant complications. Subjective evaluation by questionnaires was done in all patients. Three patients could not be evaluated objec-tively by transvaginal ultrasound, 2 patients resigned and 1 was pregnant. There was no significant difference in menorrhagia and dysmenorrhea reduction score between the 2 groups (p=0.399 and 0.213, respectively). In both groups, dysmenorrhea was reduced significantly after treatment. No significant statistical difference was found in median adenomyosis volume increment (p=0.630) be-tween the resection (median=+15.35% (-100-159)} and myolysis groups (median=+48.43% (-100-553)). Five patients were pregnant, 3 from the resection group and 2 from the myolysis group. Uterine rupture was found in 1 patient (from the myolysis group) at the age of 8 months of pregnancy. The effectiveness of laparoscopic adenomyosis resection was not significantly different compared with lapa-rascopic myolysis as an alternative conservative surgery in treating symptomatic adenomyosis. Myolysis was not recommended for women who wish to be pregnant. (Med J Indones 2006; 15:9-17)Keywords: laparascopy, resection, myolysis, conservative surgery, symptomatic adenomyosis